PENGARUH LEAN MANAGEMENT DAN SISTEM INFORMASI TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING: STUDI KASUS RS PKU MUHAMMADIYAH SEKAPUK - fahlevi, Mohammad feryzal; widodo, Agus purbo; jondar, aloysius (JEB17 : Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of Lean Management and Information Systems on Employee Performance with Job Satisfaction as an intervening variable at PKU Muhammadiyah Sekapuk Hospital. A quantitative research approach was employed using Structural Equation Modeling (SEM) with AMOS. The study population consisted of all hospital employees, with samples selected through proportional random sampling. The research instrument was a five-point Likert scale questionnaire that had been tested for validity and reliability. The results revealed that Lean Management and Information Systems have a significant positive effect on Job Satisfaction, while Job Satisfaction mediates the relationship between both independent variables and Employee Performance. Furthermore, Information Systems demonstrated a stronger direct influence on Employee Performance compared to Lean Management. The research model achieved an acceptable level of Goodness of Fit (Chi-Square=61.815; Probability=0.087; GFI=0.912; RMSEA=0.052; TLI=0.972). These findings highlight the importance of implementing lean management practices and effective information systems to enhance job satisfaction and employee performance in healthcare organizations. Keywords: Lean Management, Information Systems, Job Satisfaction, Employee Performance, SEM-AMOS